Analysis of Traffic Accident Factors on The Road of Tarahan Lampung Selatan - Kholbuniah, Megalensi; Sulistyorini, Rahayu; Purba, Aleksander; Herianto, Dwi (Universitas Lampung, 2020)
The purposes of this study were to analyze the factors causing of the traffic accident using correlation analysis with SPSS program and analyze the relationship between the characteristics of accidents and road safety facilities such as road signs, road markings, and lighting lights the road of Tarahan. The secondary data were obtained from the Ditlantas Polda Lampung in the form of accident data per month from 2014-2018. Then from National Road Planning and Supervision were obtained form of geometric data for the Tarahan Road in 2019. The results showed that there were still inadeguate road safety facilities on the Tarahan road, such as lighting, road markings and rescue path. In terms of the geometric conditions of the Tarahan Road it has a maximum slope exceeding the Bina Marga standard of 10,83%, it affects traffic accidents. The characteristics of accidents based on the factors that cause the accidents were vechicle factors (46,7%) with the result of correlation analysis of ,943* significance ,016. The types of accidents were are single accidents (35,5%) with the result of correlation analysis of ,934* significance ,020. Keywords: Accident Characteristics, Correlation, Road Safety Facilities